Fluid machinery life extension of pumps, gas compressors and drivers - Bloch, Heinz P., 1933- (De Gruyter, 2020)
"Fluid movers are extensively used in the process industries. New machines are specified, designed, manufactured and installed in a way that ensures their safety and reliability. Existing machines may be upgraded or retrofitted during maintenance or repair. This book describes how improved components and better lubricant application provisions, among other experience-based measures, can safely extend operating life and increase profitability"-- Provided by publisher.
Keywords: Turbomachines.; Fluid mechanics.; elektronické knihy; electronic books